Levodopa-Loaded 3D-Printed Poly (Lactic) Acid/Chitosan Neural Tissue Scaffold as a Promising Drug Delivery System for the Treatment of Parkinson’s Disease - Ezgi Saylam (MDPI AG, 2021)
Parkinson’s disease, the second most common neurodegenerative disease in the world, develops due to decreased dopamine levels in the basal ganglia. Levodopa, a dopamine precursor used in the treatment of Parkinson’s disease, can be used as a drug delivery system. This study presents an approach to the use of 3D-printed levodopa-loaded neural tissue scaffolds produced with polylactic acid (PLA) and chitosan (CS) for the treatment of Parkinson’s disease. Surface morphology and pore sizes were examined by scanning electron microscopy (SEM). Average pore sizes of 100–200 µm were found to be ideal for tissue engineering scaffolds, allowing cell penetration but not drastically altering the mechanical properties. It was observed that the swelling and weight loss behaviors of the scaffolds increased after the addition of CS to the PLA. Levodopa was released from the 3D-printed scaffolds in a controlled manner for 14 days, according to a Fickian diffusion mechanism. Mesenchymal stem cells (hAD-MSCs) derived from human adipose tissue were used in MTT analysis, fluorescence microscopy and SEM studies and confirmed adequate biocompatibility. Overall, the obtained results show that PLA/CS 3D-printed scaffolds have an alternative use for the levodopa delivery system for Parkinson’s disease in neural tissue engineering applications.